Economic feasibility of stationary electrochemical storages for electric bill management applications: The Italian scenario. (July 2016) - Telaretti, E.; Graditi, G.; Ippolito, M.G.; Zizzo, G.
Abstract: Battery energy storage systems (BESSs) are expected to become a fundamental element of the electricity infrastructure, thanks to their ability to decouple generation and demand over time. BESSs can also be used to store electricity during low-price hours, when the demand is low, and to meet the demand during peak hours, thus leading to savings for the consumer. This work focuses on the economic viability of BESS from the point of view of the electricity customer. The analysis refers to a lithium-ion (Li-ion), an advanced lead-acid, a zinc-based, a sodium-sulphur (NaS) and a flow battery. The total investment and replacement costs are estimated in order to calculate the cumulated cash flow, the net present value (NPV) and the internal rate of return (IRR) of the investment. A parametric analysis is further carried out under two different assumptions: a) varying the difference between high and low electricity prices, b) varying the peak demand charges. The analysis reveals that some electrochemical technologies are more suitable than others for electric bill management applications, and that a profit for the customer can be reached only with a significant difference between high and low electricity prices or when high peak demand charges are applied. Highlights: We examine the convenience of using BESS to reduce customer electricity bill. We make a comparison among different types of batteries for end-user applications. We evaluate the convenience of using storage in presence of demand charges. A parametric analysis changing the BESS cost, electricity prices and demand charges has been carried out. A case study is performed to show the advantages/disadvantages of this approach.